PENGARUH TERAPI WARNA HIJAU TERHADAP TINGKAT KECEMASAN MAHASISWA DALAM MENGHADAPI UJIAN - Ance Siallagan (Elisabeth Health Jurnal, 2020)
Introduction: Many students experience anxiety, especially when going to face an exam. The results of interviews with 10 beginning students at STIKes Santa Elisabeth Medan obtained data that 3 people experienced severe anxiety, 5 people experienced moderate anxiety and 2 people experienced mild anxiety just before the test. They experience sleep disturbances and lack of rest, decreased appetite, fast heart beat, frequent urination, decreased concentration of learning, and feel anxious to remember the exam is getting closer. Method: This type of research is pre-experimental with one-group pre-post test design research. The study was conducted at STIKes Santa Elisabeth Medan in March-April 2018. The total sample of 15 people with a sampling technique was purposive sampling by selecting samples based on criteria set by researchers. The study was conducted using an anxiety level questionnaire instrument and standard operating procedures for color therapy. The data obtained were analyzed using the Wilcoxon sign rank test, at a 95% confidence level.Result: Based on the results of the analysis, it is known that there is an effect of green color therapy on changes in the level of student anxiety in facing exams. Discussion: The green color causes an increase in serotonin levels which has an important role to control sleep-wake, eating behavior, controlling sensory transmission, mood, and a number of behaviors. Providing green color therapy will stimulate the release of serotonin, so that increased levels of serotonin can improve one's mood so that it can create a sense of happiness and reduce anxiety. Someone who is given green color therapy can help individuals to be able to control themselves and focus attention so that the individual can take the right response when in a tense situation. In this study, after being given the intervention of green color therapy respondents who have severe to moderate anxiety levels. While those who have moderate anxiety become mild anxiety. green color therapy can affect changes in student anxiety levels.